The Causes of Unauthorized Residential Plots Development and Implication for Government Agencies (Sains Humanika, 2022)
Rising house prices, particularly in emerging areas, have prompted some people to look for new ways to buy a home by purchasing residential plots of land. Additionally, because the city's development is more oriented toward strata development, some people want to possess a landed house, which is more comfortable. Bungalow lots, lot lidi, tiny plots, and house lots are all terms used to describe land sold as a residential plot. However, problems arise when residential plots are developed that do not adhere to the law's standards and guidelines, resulting in the creation of residential plots without permission becoming more common. The purpose of this study was to determine the causes of the rise in unauthorized residential plot development, as well as the ramifications for government agencies. Mukim Ijok and Mukim Jeram in Kuala Selangor were chosen as case studies using a qualitative approach. The interview session included a total of 13 respondents, chosen by purposive sampling. According to the findings of this study, there are four (4) major causes that contribute to the rise in the development of unauthorized residential plots: high profit margins for landowners, rising house prices, the desire to own a house on their own land for a lower price, and a lack of knowledge about land among owners and buyers. While, the implications of these issues for government authority were economic, social, and environmental in nature. Finally, the study's findings are likely to improve community awareness of the detrimental implications of unauthorised residential plot development.
Keywords: Implikasi, lot lidi, plot kediaman, punca, tanpa kebenaran